Predictive value of serum iron on heart failure in patients with acute ST‐segment elevation myocardial infarction. Issue 4 (13th February 2023) - Chen, Wen; Lin, Guoli; Dai, Caizhi; Xu, Kaizu
Abstract: Background: In clinical practice, heart failure often occurs after acute myocardial infarction, and a new biomarker for its early prediction is urgently needed. The aim of this study was to investigate the relationship between serum iron and heart failure after acute ST‐segment elevation myocardial infarction (STEMI). Methods: A total of 41 patients with heart failure after STEMI and 31 controls were included in the study. The demographic variables and baseline clinical characteristics of both groups were analyzed. Results: There were no significant differences between patients with heart failure and controls in terms of demographic characteristics. There were significant differences in terms of serum iron, N terminal pro‐B‐type natriuretic peptide levels, left atrial diameter, and left ventricular ejection fraction. Binary logistic regression analyses demonstrated that serum iron (odds ratio [OR]: 0.804, 95% confidence interval [CI]: 0.699–0.924) and Tn‐I (OR: 1.072, 95% CI: 1.011–1.137) were independent predictors for heart failure ( p  < .05, respectively). Receiver operating characteristic analysis showed that the area under the curve for serum iron was 0.808 (95% CI: 0.707–0.908, p  < .01). The best cutoff value of serum iron was 11.87 μmol/L (sensitivity: 87.1%; specificity: 68.3%). Conclusions: Patients with heart failure after STEMI have lower serum iron levels than patients without heart failure after STEMI. Serum iron levels are a risk factor for heart failure after STEMI. Abstract : Different levels of serum iron in ST‐segment elevation myocardial infarction.